Engineered Nanomaterials - Health and Safety 2020
DOI: 10.5772/intechopen.89344
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanoparticles Using Heterotheca inuloides and Its Antimicrobial Activity in Catgut Suture Threads

Abstract: Silver nanoparticles were synthesized through a green method, using Heterotheca inuloides as a bioreducing agent. Moreover, catgut suture threads were decorated with those biogenic silver nanoparticles, and their antibacterial activity versus highly resistant pathogenic microorganisms was evaluated. The principles of green chemistry and nanotechnology allow us to obtain advanced materials, such as suture threads, which can reduce or avoid the prevalence of infectious processes in the medical field. Mexican med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The most significant peaks of the bovine bone powder are found at 2970 cm −1 (CH 2 asymmetric stretch), 1445 cm −1 , and 1414 cm −1 (CH 2 wagging and bending vibrations and CO 3 2− ), 1016 cm −1 (PO 4 3− asymmetric stretch), 873 cm −1 (CO 3 2− bending vibrations), 600 cm −1 , and 560 cm −1 (PO 4 3− bending vibrations), these functional groups are characteristic of hydroxyapatite and collagen, the main components of bovine bone powder [49,50]. Likewise, in Figure 8, the Ag nanoparticles supported on BBP sample (red spectrum), minor peaks were found at the following wavelengths, 1375 cm −1 (C-O stretch), 1535 cm −1 (C=C-C stretch), and 2924 cm −1 (CH stretch, OHstretch of aliphatic acids), which can be attributed to the functional groups corresponding to polyphenols, phenols, and sesquiterpene compounds [51][52][53]. Moreover, comparing the Ag-BBP (red) and bare BBP (blue) spectra, it is possible to observe a decrease in the peaks at 600 cm −1 560 cm −1 and 1016 cm −1 , corresponding to PO 4 3− functional groups of hydroxyapatite, and 1445 cm −1 and 1414 cm −1 corresponding to CO 3 2− groups of collagen.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 82%
“…The most significant peaks of the bovine bone powder are found at 2970 cm −1 (CH 2 asymmetric stretch), 1445 cm −1 , and 1414 cm −1 (CH 2 wagging and bending vibrations and CO 3 2− ), 1016 cm −1 (PO 4 3− asymmetric stretch), 873 cm −1 (CO 3 2− bending vibrations), 600 cm −1 , and 560 cm −1 (PO 4 3− bending vibrations), these functional groups are characteristic of hydroxyapatite and collagen, the main components of bovine bone powder [49,50]. Likewise, in Figure 8, the Ag nanoparticles supported on BBP sample (red spectrum), minor peaks were found at the following wavelengths, 1375 cm −1 (C-O stretch), 1535 cm −1 (C=C-C stretch), and 2924 cm −1 (CH stretch, OHstretch of aliphatic acids), which can be attributed to the functional groups corresponding to polyphenols, phenols, and sesquiterpene compounds [51][52][53]. Moreover, comparing the Ag-BBP (red) and bare BBP (blue) spectra, it is possible to observe a decrease in the peaks at 600 cm −1 560 cm −1 and 1016 cm −1 , corresponding to PO 4 3− functional groups of hydroxyapatite, and 1445 cm −1 and 1414 cm −1 corresponding to CO 3 2− groups of collagen.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 82%
“…aureus, Escherichia coli, Pseudomonas aeruginosa, Acinetobacter baumannii, and Klebsiella pneumoniae) compared to the uncoated specimen. Guadarrama-Reyes et al decorated the cat gut sutures with biologically synthesized AgNPs using Heterotheca inuloides and evaluated their antibacterial activity against E. coli and S.…”
Section: Discussionmentioning
confidence: 99%
“…Syukri et al 40 coated nylon monofilament surgical sutures with biogenic silver nanoparticles and inferred that coated sutures exhibited a high bactericidal activity on wound pathogens ( S. aureus , Escherichia coli , Pseudomonas aeruginosa , Acinetobacter baumannii , and Klebsiella pneumoniae ) compared to the uncoated specimen. Guadarrama-Reyes et al 41 decorated the cat gut sutures with biologically synthesized AgNPs using Heterotheca inuloides and evaluated their antibacterial activity against E. coli and S. aureus . They suggested that this suture might be used alternatively to help reduce the excess antibiotic use.…”
Section: Discussionmentioning
confidence: 99%